(untitled) (Bangladesh Journal of Urology, 2023)
Background:Transmesocolic (TMC) approachis an alternative approach to ureteropelvic junction (UPJ) that has been shown to reduce operative time compared to the standard laterocolic (LC) approach during laparoscopic pyeloplasty. It offers a direct path to the left UPJ through the mesocolon with less tissue dissection and bowel manipulation. In this study we evaluated the outcome of transmesocolic (TMC) laparoscopic pyeloplasty compared with conventional laterocolic procedure. Materials and Methods: We started laparoscopic pyeloplasty for ureteropelvic junction obstruction in 2015. Since then, 56 patients of left side disease have undergone this surgery in our institution. To access the left ureteropelvic junction, we used the conventional latero-colic (LC) approach in 33 patients, while the transmesocolic (TMC) approach was used in the remaining 23 patients, and perioperative results and follow-up data were then compared. Results: The mean operative time using the transmesocolic approach was significantly shorter than the conventional laterocolic approach (97 vs. 160 min, p=0.022). Furthermore, there was no complication or open conversion. In early postoperative period, 1 (3.03%) patient in laterocolic approach group developed ileus. Postoperative pain, mean hospital stay was similar in both groups. All patients were symptom-free after 1 year of follow-up, and radiologic success rates for each group were 90 and 88%, respectively. Conclusion: Direct exposure of the ureteropelvic junction via the mesocolon saves time during the colon mobilization procedure. The approach is safe and feasible and has success rates similar to those of the conventional laterocolic approach. Bangladesh J. Urol. 2023; 26(1): 40-43